The role of clinical psychologist in speech and hearing clinic - J, Bharath Raj (Journal of All India Institute of Speech and Hearing, 1970)
The idea of application of Clinical Psychology in the speech and hearing set up, first came to my mind about 3 years ago, when the Department of Clinical Psychology had to be started afresh at the All India Institute of Speech and Hear- ing, Mysore. The departmental work had to be geared to the needs of the speech and hearing clinic